(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. This article discusses bovine cysticercosis and its preventive measures. Cysticercosis is a common parasitic disease in cattle, primarily caused by the parasite Taenia saginata. Due to its widespread occurrence and the threat it poses to human health, the disease causes significant economic losses in the livestock industry. The paper provides both theoretical and practical information on the epizootiology, pathogenesis, clinical symptoms, diagnostic methods, and preventive measures related to the disease. Furthermore, based on statistical data and practical observations from different regions of Uzbekistan, the article offers recommendations for preventing the disease.